Drug Delivery Implants in the Treatment of Vitreous Inflammation - Jillian Wang; Angela Jiang; Malav Joshi; John Christoforidis (Hindawi Limited, 2013)
The eye is a model organ for the local delivery of therapeutics. This proves beneficial when treating vitreous inflammation and other ophthalmic pathologies. The chronicity of certain diseases, however, limits the effectiveness of locally administered drugs. To maintain such treatments often requires frequent office visits and can result in increased risk of infection and toxicity to the patient. This paper focuses on the implantable devices and particulate drug delivery systems that are currently being implemented and investigated to overcome these challenges. Implants currently on the market or undergoing clinical trials include those made of nonbiodegradable polymers, containing ganciclovir, fluocinolone acetonide, triamcinolone acetonide, and ranibizumab, and biodegradable polymers, containing dexamethasone, triamcinolone acetonide, and ranibizumab. Investigational intravitreal implants and particulate drug delivery systems, such as nanoparticles, microparticles, and liposomes, are also explored in this review article.